Pengaruh Product Attribute Dan Customer Trust Terhadap Customer Loyalty Melalui Customer Value Dan Customer Satisfaction Sebagai Variabel Mediasi Pada Pelanggan Indomaret Di Jakarta Barat - Rejeki, Sri; Ria Atmaja, Dodi (CV. Lafadz Jaya, 2022)
Indomaret plays a very important role in the retail industry in Indonesia, especially in West Jakarta, now a days many consumers choose Indomaret as their main shopping place for their daily needs and are very selective in buying a product. The purpose of this study is to determine the factors that can affect customer loyalty such as product attributes, customer value, customer satisfaction, and customer trust. This research was conducted on 155 respondents in West Jakarta who are Indomaret customers by collecting online questionnaire data conducted in July 2022. Researchers used the structural equation model (SEM) analysis method with SmartPLS software to test this research. The results obtained indicate that product attributes have a positive and significant effect on customer value, product attributes have no significant effect on customer loyalty, customer value has no significant effect on customer loyalty, customer trust has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, customer trust has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect as a partial mediation between customer trust and customer loyalty, customer value has no significant effect between product attributes and customer loyalty so it cannot mediate between these variables.